Protein Aggregation Inhibitors as Disease-Modifying Therapies for Polyglutamine Diseases - Minakawa, Eiko N.; Nagai, Yoshitaka (Frontiers in Neuroscience, 2021)
The polyglutamine (polyQ) diseases are a group of inherited neurodegenerative diseases caused by the abnormal expansion of a CAG trinucleotide repeat that are translated into an expanded polyQ stretch in the disease-causative proteins. The expanded polyQ stretch itself plays a critical disease-causative role in the pathomechanisms underlying polyQ diseases. Notably, the expanded polyQ stretch undergoes a conformational transition from the native monomer into the β-sheet-rich monomer, followed by the formation of soluble oligomers and then insoluble aggregates with amyloid fibrillar structures. The intermediate soluble species including the β-sheet-rich monomer and oligomers exhibit substantial neurotoxicity. Therefore, protein conformation stabilization and aggregation inhibition that target the upstream of the insoluble aggregate formation would be a promising approach towards the development of disease-modifying therapies for polyQ diseases. PolyQ aggregation inhibitors of different chemical categories, such as intrabodies, peptides, and small chemical compounds, have been identified through intensive screening methods. Among them, recent advances in the brain delivery methods of several peptides and the screening of small chemical compounds have brought them closer to clinical utility. Notably, the recent discovery of arginine as a potent conformation stabilizer and aggregation inhibitor of polyQ proteins both in vitro and in vivo have paved way to the clinical trial for the patients with polyQ diseases. Meanwhile, expression reduction of expanded polyQ proteins per se would be another promising approach towards disease modification of polyQ diseases. Gene silencing, especially by antisense oligonucleotides (ASOs), have succeeded in reducing the expression of polyQ proteins in the animal models of various polyQ diseases by targeting the aberrant mRNA with expanded CAG repeats. Of note, some of these ASOs have recently been translated into clinical trials. Here we overview and discuss these recent advances towards the development of disease modifying therapies for polyQ diseases. We envision that combination therapies using aggregation inhibitors and gene silencing would meet the needs of the patients with polyQ diseases and their caregivers in the near future to delay or prevent the onset and progression of these currently intractable diseases.